Use of high-throughput mass spectrometry to elucidate host––pathogen interactions in Salmonella. (December 2008) - Rodland, Karin D; Adkins, Joshua N; Ansong, Charles; Chowdhury, Saiful; Manes, Nathan P; Shi, Liang; Yoon, Hyunjin; Smith, Richard D; Heffron, Fred
Capabilities in mass spectrometry are evolving rapidly, with recent improvements in sensitivity, data analysis and, most important from the standpoint of this review, much higher throughput, allowing analysis of many samples in a single day. This short review describes how these improvements in mass spectrometry can be used to dissect host––pathogen interactions using Salmonella as a model system. This approach has enabled direct identification of the majority of annotated Salmonella proteins, quantitation of expression changes under various in vitro growth conditions and new insights into virulence and expression of Salmonella proteins within host cells. One of the most significant findings is that a relatively high percentage of all the annotated genes (>20%) in Salmonella are regulated post-transcriptionally. In addition, new and unexpected interactions have been identified for several Salmonella virulence regulators that involve protein––protein interactions, suggesting additional functions of these regulators in coordinating virulence expression. Overall high-throughput mass spectrometry provides a new view of host––pathogen interactions, emphasizing the protein products and defining how protein interactions determine the outcome of infection.